Diagnostic accuracy of optical coherence tomography for surgical margin assessment of feline injection‐site sarcoma. (14th September 2021) - Coleman, Mary J.; Selmic, Laura E.; Samuelson, Jonathan P.; Jennings, Ryan; Huang, Pin‐Chieh; McLaughlin, Eric M.; Wavreille, Vincent A.; Dornbusch, Josephine A.; Lapsley, Janis; Howard, James; Cheng, Edward; Kalamaras, Alex; et al.
Abstract: The invasive, locally aggressive nature of feline injection‐site sarcomas (FISSs) poses a unique challenge for surgeons to obtain complete margins with surgical excision. Optical coherence tomography (OCT), an imaging technology that uses light waves to generate real‐time views of tissue architecture, provides an emerging solution to this dilemma by allowing fast, high‐resolution scanning of surgical margins. The purpose of this study was to use OCT to assess surgical margins of FISS and to evaluate the diagnostic accuracy of OCT for detecting residual cancer using six evaluators of varying experience. Five FISSs were imaged with OCT to create a training set of OCT images that were compared with histopathology. Next, 25 FISSs were imaged with OCT prior to histopathology. Six evaluators of varying experience participated in a training session on OCT imaging after which each of the evaluators was given a dataset that included OCT images and videos to score on a scale from cancerous to non‐cancerous. Diagnostic accuracy statistics were calculated. The overall sensitivity and specificity for classification of OCT images by evaluators were 78.9% and 77.6%, respectively. Correct classification rate of OCT images was associated with experience, while individual sensitivities and specificities had more variation between experience groups. This study demonstrates the ability of evaluators to correctly classify OCT images with overall low levels of experience and training and also illustrates areas where increased training can improve accuracy of evaluators in interpretation of OCT surgical margin images.